TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA OLEH ANGGOTA KEPOLISIAN REPUBLIK INDONESIA - Akmal Muhammad Rizqia Rahman (Kajian Hukum, 2021)
Drug abuse is a very worrying crime in various parts of the world, including Indonesia. Narcotics abuse is a transnational crime (transnational crime), organized crime, and serious crime that can affect various levels of society. The government's steps through the National Narcotics Agency need to be supported by legal regulations related to narcotics abuse which need to be enforced by law enforcement officers or commonly called law enforcement officers. If there is a criminal act of narcotics abuse, the ones who follow up on the crime are law enforcement officers, namely the Police, Prosecutors, Judges. This research is a normative or doctrinal legal research. The data used is secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. This paper concludes that the process of enforcing the code of ethics for the police profession against members of the police who are caught in a criminal case of narcotics abuse will be examined and if proven, they will be subject to sanctions. The imposition of disciplinary sanctions and sanctions for violations of the code of ethics does not remove criminal charges against the police officers concerned. Police officers who use narcotics will still be prosecuted even though they have undergone disciplinary sanctions and sanctions for violating the code of ethics. Police officers who are suspected of using narcotics and subject to investigation must still be considered innocent until proven through a court decision that has permanent legal force